Implementation of JSON Parsing in Agricultural Productive Learning Applications - Abdul Rahman Ismail; Ifriandi Labolo; Yuni Handayani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The learning process at SMK Negeri 1 Mootilango is still conventional, in other words that the teaching and learning process between students and teachers can only be carried out with the condition that there are meetings between students and teachers in the classroom. If a meeting between students and teachers does not occur or the teacher concerned is not present and learning time is limited by the school, then the learning process will automatically be hampered. One of the teaching methods that is currently developing is mobile learning. Mobile Learning can assist teachers in distributing their teaching materials without having to be in class by using the internet, this can maximize learning time in limited classes. In making software using the Waterfall method. The data collection method used in this research is literature study, observation and interviews or interviews with the topic to be taken. This application is designed using Java programming language software, namely Android Studio, for PHP and HTML programming languages using Sublime Lite software, and for data storage using MySQL, as well as tools for modeling using UML (Unified Modeling Language). Based on the results of the Whitebox test on one of the processes in this system, namely on the evaluation menu with balanced Cyclometic Complexity (CC) = 4 results, this system is stated to be able to run well. While the results of testing the Blackbox system can run as expected.